2018
DOI: 10.1155/2018/6901751
|View full text |Cite
|
Sign up to set email alerts
|

Amoebic Liver Abscess and Indigenous Alcoholic Beverages in the Tropics

Abstract: Amoebic liver abscess (ALA) seen commonly in the tropics is predominantly confined to adult males, especially those who consume locally brewed alcohol, although intestinal amoebiasis occurs in all age groups and in both genders. Whether the role of alcohol in the development of ALA is incidental and casual or whether alcohol is causally implicated has been debated. It has been argued that socioeconomic factors and poor sanitary conditions are the primary culprits that casually link alcohol to ALA. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
(41 reference statements)
1
13
0
Order By: Relevance
“…This finding contradicts with a laboratory-based study that found testosterone increased the susceptibility of mice to Entamoeba histolytica liver abscess by reducing the interferon-gamma secretion by natural killer cells but human studies are lacking. 11 A further, well designed prospective cohort study would be favorable to explore this observation. It has been suggested, based on animal models (hamster), that the male hormone testosterone could be a host factor that favors the development of ALA. 4 The positive role of testosterone could be one of the explanations that middle-aged men were mostly affected, with ALA reaching a peak by the age of 40 years.…”
Section: Discussionmentioning
confidence: 97%
“…This finding contradicts with a laboratory-based study that found testosterone increased the susceptibility of mice to Entamoeba histolytica liver abscess by reducing the interferon-gamma secretion by natural killer cells but human studies are lacking. 11 A further, well designed prospective cohort study would be favorable to explore this observation. It has been suggested, based on animal models (hamster), that the male hormone testosterone could be a host factor that favors the development of ALA. 4 The positive role of testosterone could be one of the explanations that middle-aged men were mostly affected, with ALA reaching a peak by the age of 40 years.…”
Section: Discussionmentioning
confidence: 97%
“…Ultimately, the progression to symptomatic disease is dependent on a multitude of factors including gut microbiome composition, dysbiosis, hosts' age, hosts' genetic composition, immunogenicity (i.e., reduced cellmediated immunity), and the unique interaction between host-immunity and parasitic virulence. These have been shown to be a predictor of disease severity [9,[52][53][54][55], and are discussed in Fig. 1 below.…”
Section: Pathogenesis Of Entamoeba Histolyticamentioning
confidence: 97%
“…The first published report of E. histolytica in Sri Lanka dates back to 1962 [7]. Since then, numerous studies have highlighted the burden of this disease as a major public health concern [6,7,9,11,47]. In 1985, ALA accounted for 5.9% of total admissions at the Teaching Hospital Jaffna (THJ) [4].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations